Dignity, discourse, and destiny the life of Courtney C. Smith - Stapleton, Darwin H.; Heckman Stapleton, Donna (Newark University of Delaware Press, 2004)
Childhood -- Harvard, Oxford, and marriage -- In the Navy -- Return to education : Princeton -- The Woodrow Wilson Program years -- Swarthmore College at mid-century -- Swarthmore looks for Courtney -- Inauguration -- The case for the liberal arts college -- Faculty -- "There is strength-- in having a variety of sources of support" : funding the liberal arts tradition -- Networks of support and service : behind the presidency -- "Nature shaped to advantage" : preserving campus viability -- Student activism : "to care about social justice" -- Two decades of student life at Swarthmore -- "Personal things" -- Administration of a college -- The final year -- Conclusion
Childhood -- Harvard, Oxford, and marriage -- In the Navy -- Return to education : Princeton -- The Woodrow Wilson Program years -- Swarthmore College at mid-century -- Swarthmore looks for Courtney -- Inauguration -- The case for the liberal arts college -- Faculty -- "There is strength-- in having a variety of sources of support" : funding the liberal arts tradition -- Networks of support and service : behind the presidency -- "Nature shaped to advantage" : preserving campus viability -- Student activism : "to care about social justice" -- Two decades of student life at Swarthmore -- "Personal things" -- Administration of a college -- The final year -- Conclusion
Includes bibliographical references (p. 239-242) and index
Archivierung prüfen
Keywords: Smith, Courtney C -- 1916-; Swarthmore College -- Presidents -- Biography; College presidents -- United States -- Biography; Bibliografie